Peran Manajemen Pemasaran Relasional dan Kualitas Pelayanan dalam Membentuk Loyalitas Pelanggan di Hotel Bin Daod - Fitriya Ukhra; Yusnaidi Yusnaidi; Mardaleta Mardaleta (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of relationship marketing management and service quality on customer loyalty at Bin Daod Hotel. Customer loyalty is an important factor in maintaining the sustainability of hotel businesses amidst increasingly intense competition. Relationship marketing management and service quality are considered factors that can build long-term relationships and increase customer loyalty to the hotel. This study employed a quantitative approach with an associative research design. The population consisted of all customers who had used the services of Bin Daod Hotel. The sampling technique used was purposive sampling, resulting in 107 respondents. Data were collected through questionnaires measured using a Likert scale. Data analysis was conducted using multiple linear regression supported by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination (R²). The results indicate that relationship marketing management has a positive and significant effect on customer loyalty. Service quality also has a positive and significant effect on customer loyalty. Furthermore, relationship marketing management and service quality simultaneously have a positive and significant effect on customer loyalty at Bin Daod Hotel. These findings suggest that the better the implementation of relationship marketing management and service quality, the higher the level of customer loyalty toward Bin Daod Hotel.